DNA BARCODING OF HARIMONTING (RHODOMYRTUS TOMENTOSA) USING THE TRNL-F GENE - Khaira MS, Nazlil; Tambunan, Efrida Pima Sari; Idami, Zahratul (BEST Journal (Biology Education, Sains and Technology), 2024)
DNA Barcoding is one or more short gene sequences taken from a standard part of the genome and used to identify species. Harimonting plant is a wild plant, but in some places this plant is used as an ornamental plant. This study aims to determine the molecular characteristics of the trnL-F gene in Rhodomyrtus tomentosa, to determine the genetic diversity of Rhodomyrtus tomentosa using the trnL-F gene, and to examine the phylogenetic relationships of Rhodomyrtus tomentosa using the trnL-F gene. This research method was carried out in stages: sample collection, DNA isolation, PCR (Polymerase Chain Reaction), electrophoresis, sequencing and analysis of sequence results. Morphological characterization of Rhodomyrtus tomentosa plants collected from Tara Bunga Hill was seen from the results of DNA barcodes and observations of visible morphological characters and literature studies. The results of the Rhodomyrtus tomentosa DNA barcode from the results of molecular analysis of Rhodomyrtus tomentosa obtained the results of a sequence of 359 bp. The plant sequences of Rhodomyrtus tomentosa were analyzed using the MEGA 11 application. Genetic distance calculation (pairwise distance), GC content calculation, and nucleotide diversity were performed. Calculation of GC content showed that the value of GC content in Rhodomyrtus tomentosa was lower than AT content which indicated that Rhodomyrtus tomentosa species were more primitive. Based on the phylogenetic tree reconstruction, all species are divided into 2 clades.